Pembinaan Potensi Kearifan Lokal dalam Mewujudkan Generasi Muda Hindu Sadar Wisata - Rieka Yulita Widaswara; Ni Putu Sasmika Dewi; Sayu Kadek Jelantik; I Ketut Putu Suardana; Ni Nyoman Harnika (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
Community Service Activities carried out by the Cultural and Religious Tourism Study Program in 2021 in Karang Kubu Hamlet, Bilebante Village, Pringgarata District, Central Lombok Regency, NTB Province. This hamlet was chosen as the location of the dedication because it has the potential for local wisdom, especially for the younger generation of Hindus, besides that Bilebante village is a tourist village that has beautiful natural charm. The methods used in this service are lectures, discussions and also practices which are carried out for five days from morning to evening. As for the results of the coaching, namely the practice of praying together between the temple implementing team and community members, especially the younger generation of Hindus. Furthermore, there is development of regional dances, namely Balinese dance, yoga coaching, public speaking for dharma discourse and also master of ceremonies, and also creation of promotional video content for the Bilebante tourist village by exploring the beauty of the village with narration using three languages, namely Balinese as a regional language, Indonesian. as the national language and English as the international language. The video content is expected to become a promotional event for the Bilebante tourist village through digital media.